Williams and Morrone misunderstand and inadvertently support my argument: Mexico’s SNI systematically steers ecological research - Neff, Mark W (Science and Public Policy, 2019)
Abstract My recent publication highlighting the unintended steering influences of publication incentives on the research agenda of Mexican ecological scientists elicited a vehement critique from two renowned Mexican ecologists, Williams and Morrone. The argument I advance is that Mexico’s National System of Researchers (SNI) unintentionally steers ecological researchers away from the knowledge needs of local, national, and regional users of scientific knowledge and relinquishes research priority-setting to individuals and institutions disconnected from Mexico’s knowledge needs. Rather than engaging with the substance of argument, these critics focus on what they believe to be factual errors. In their response, Williams and Morrone effectively but unintentionally confirm the premise, mechanism, and indeed the key factual claims in my article. I stand behind my analysis as published.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTA5My9zY2lwb2wvc2N5MDMx